Assessment of composted kitchen waste and poultry manure amendments on growth, yield and heavy metal uptake by Jute mallow Corchorus olitorius Linn. - Oladele A. Oguntade; Titilola S. Olagbenro; Olubunmi A. Odusanya; Solomon O. Olagunju; Kayode M. Adewusi; Adedotun T. Adegoke (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose This study was carried out to compare the effects of composted kitchen waste (KW) and poultry manure (PM) soil amendments on growth, yield and heavy metal uptake in edible leaf of Corchorus olitorius. Methods Kitchen waste and PM composted for 8 weeks were applied as soil amendment at the rate of 0 (no amendment), 5, 10 and 15 t ha−1. Corchorus seeds were sown 2 weeks after incorporation of amendment. Compost amendments were the main treatments while application rates were in sub-plots. Treatments were replicated three times in a randomized complete block design. Corchorus were harvested 6 weeks after sowing, following which growth and yield parameters were measured. Concentrations of manganese (Mn), iron (Fe), copper (Cu) and zinc (Zn) in leaf tissue and plant uptake were also determined. Results Result showed that PM increased Corchorus leaf production than KW. Poultry manure significantly (p ≤ 0.01) increased Cu accumulation in leaf. Bioaccumulation of Cu was 0.005 and 0.011 mg kg−1 for KW and PM, respectively. The metals except Zn in leaf tissue showed significant (p ≤ 0.01) correlation with both fresh and dry weights of Corchorus. Despite high concentration of heavy metals in the compost, bioaccumulation in leaf was lower than maximum allowable limit of 0.1 mg kg−1 for Cu and 0.3 mg kg−1 for Mn, Fe and Zn in vegetables by WHO/FAO/FEPA. Conclusion Soil amended with composted KW and PM promoted Corchorus growth and yield. Accumulations of heavy metals in leaf tissue are within allowable limit for vegetables.